Analisis Pendapatan Usaha Jagung Giling dan Jagung Biji di Desa Langir Kecamatan Kangae Kabupaten Sikka - Hendrikus Darwin Beja; Akbar Hidayatullah Zaini (Agriculture - Jurnal Ilmu Pertanian, 2025)
A study was conducted in Langir Village, Kangae District, Sikka Regency from February 2024. The purpose of this study was to determine how much income was obtained from the milled corn and seed corn business and to determine how much relative profit was obtained from the milled corn and seed corn business in Langir Village, Kangae District, Sikka Regency. The results of the study showed that the income received by respondent farmers for the milled corn business was an average of Rp. 1,409,644, - with the lowest income of Rp. 290,000, - and the highest income of Rp. 3,627,500, -. While the income received by respondent farmers for the seed corn business was an average of Rp. 2,285,458, - with the lowest income of Rp. 30,500, - and the highest income of Rp. 15,087,500, -. From the results of the analysis, it can be concluded that selling corn in the form of seed corn or seeds is more profitable than milled corn even though both are economically profitable. This occurs when corn kernels are sold for seed. The R/C ratio for a corn milling business is 4, categorizing it as feasible because it is greater than 1. Meanwhile, the R/C ratio for a corn kernel business is 6, which, according to the criteria, is greater than 1, making it feasible. Therefore, both businesses are considered feasible.